Syphilis Testing as a Proxy Marker for a Subgroup of Men Who Have Sex With Men With a Central Role in HIV-1 Transmission in Guangzhou, China - Huang, Liping; Wu, Hao; Yan, Huanchang; Liang, Yuanhao; Li, Qingmei; Shui, Jingwei; Han, Zhigang; Tang, Shixing (Frontiers in Medicine, 2021)
Objectives: To distinguish the role of men who have sex with men (MSM) with or without syphilis testing in HIV-1 transmission and to provide molecular evidence of syphilis testing as a proxy marker for identifying the sub-group of MSM. Methods: HIV-1 transmission clusters were constructed by HIV-TRACE and Cluster Picker using HIV-1 pol sequences from 729 newly diagnosed HIV-infected MSM from 2008 to 2012 in Guangzhou, China. The role of MSM in the HIV-1 transmission networks was determined by a node influence measurement and centrality analysis. The association between syphilis testing and factors related to HIV-1 transmission and antiretroviral treatment (ART) were analyzed by the Cox regression model. Results: Among HIV-infected MSM, 56.7% did not test for syphilis at the time of HIV-1 diagnosis. MSM without syphilis testing was a specific sub-group of MSM with bigger closeness centrality and clustering coefficient than the recipients of syphilis testing (P<0.001), indicating their central position in the HIV-1 transmission networks. The median degree and radiality within HIV-1 transmission networks as well as the median K shell scores were also greater for MSM without syphilis testing (P<0.001), suggesting their relatively greater contribution in transmitting HIV-1 than the receipts of syphilis testing. The MSM without syphilis testing usually did not disclose their occupation or were more likely to be unemployed or to take non-skilled jobs, to have a history of sexually transmitted infections (STIs) and to be AIDS patients when diagnosed with HIV-1 infection (P<0.05). Multivariable Cox regression analysis indicated that syphilis testing per se did not promote the engagement of ART (p=0.233) or affect the speed of CD4+ T cell count recovery after treatment (p=0.256). Conclusions: Our study identifies syphilis testing as a proxy marker of a specific subgroup of HIV-infected MSM who refuse syphilis testing during HIV-1 diagnosis with an important role in HIV-1 transmission. Specific prevention and intervention targeting MSM without syphilis testing during HIV-1 care are urgently needed.